2010
DOI: 10.1007/s00247-010-1876-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI in osteosarcoma for evaluation and prediction of chemotherapy response: correlation with histological necrosis

Abstract: In osteosarcoma, chemotherapy response can be predicted and evaluated by conventional and diffusion-weighted MRI early in the disease course and it correlates well with necrosis. Further, newly derived parameter diffusion per unit volume appears to be a sensitive substitute for response evaluation in osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 31 publications
4
85
0
Order By: Relevance
“…However, there have been conflicting results. Other studies have not identified a significant association between ADC value and tumor necrosis (23,26,28). Therefore, the predictive value of ADC remained undetermined.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, there have been conflicting results. Other studies have not identified a significant association between ADC value and tumor necrosis (23,26,28). Therefore, the predictive value of ADC remained undetermined.…”
Section: Discussionmentioning
confidence: 94%
“…Using the predefined electric literature databases, we identified 80 potentially eligible articles, of which 72 were excluded due to duplication or after reviewing the article title and abstract. Subsequently, 3 articles were excluded after reviewing the whole article (23)(24)(25). Five articles with 106 patients who fulfilled all of the inclusion criteria were selected for the meta-analysis (Table I) (26)(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…However, conventional chemotherapeutic agents not only elicit cell apoptosis, but also induce cell necrosis (27). Song et al (10) reported that following chemotherapy, the rate of tumor cell necrosis in control group tumors was increased by approximately 50%, regardless of tumor volume and location.…”
Section: Discussionmentioning
confidence: 99%
“…The current standard of chemotherapy response evaluation is to histologically assess the tumor necrosis of the excised lesion (2,3), which has been reported to be the most important prognostic factor in osteosarcoma after neoadjuvant chemotherapy (4). However, because tumor necrosis can be assessed only in the resected specimens after the completion of neoadjuvant chemotherapy, the continuation of ineffective chemotherapy can cause the development of resistant clones (3). To overcome these limitations, noninvasive imaging modalities including bone scintigraphy (5), CT (6), MR imaging (2,3,7,8), and 18 F-FDG PET (9)(10)(11) have been investigated to predict the effect of neoadjuvant chemotherapy.…”
mentioning
confidence: 99%